Chromosome condensation and decondensation during mitosis. (June 2016) - Antonin, Wolfram; Neumann, Heinz
Graphical abstract: Highlights: Chromatin condensation and decondensation are still ill-defined in molecular terms. Chromatin condensation is driven by condensins and interactions between histones. Chromatin decondensation requires the ATPases p97 and RuvBL1/2. Abstract : During eukaryotic cell division, nuclear chromatin undergoes marked changes with respect to shape and degree of compaction. Although already significantly compacted during interphase, upon entry into mitosis chromatin further condenses and individualizes to discrete chromosomes that are captured and moved independently by the mitotic spindle apparatus. Once segregated by the spindle, chromatin decondenses to re-establish its interphase structure competent for DNA replication and transcription. Although cytologically described a long time ago, the underlying molecular mechanisms of mitotic chromatin condensation and decondensation are still ill-defined. Here we summarize our current knowledge of mitotic chromatin restructuring and recent progress in the field.